Male-mediated developmental toxicity - Brinkworth, Martin H.; Anderson, Diana (Issues in toxicology., 2007)
The issue of male germ line mutagenesis and the effects on developmental defects in the next generation has become increasingly high profile over recent years. Mutations are thought to be becoming more prevalent as a result of: exposure to chemicals in the environment, anti cancer regimes that use genotoxic agents and assisted conception techniques. In addition to the increasing frequency of mutations in the general population, attention is also being given to the effects of epigenetic events on future generations. Male-mediated Developmental Toxicity discusses these issues comprehensively and includes further analysis on the fundamental mechanisms of mutations. With both clinical and experimental sections, written by leading experts in the field, this book will appeal to both medical practitioners and researchers.